The changing roles of local government in education - Campbell, Carol (2000)
This article explores the ongoing debate about the changing roles of local government in education in Britain. It focuses on research evidence from Scotland, especially issues associated with devolving management to schools and reorganising local government. These findings are compared with the debate and evidence about the changing role of local government in education in England and Wales during the past decade. It is suggested that while there has been substantial reform of education and local government throughout Britain, the policies have differed in nature and outcomes north and south of the border. - Reproduced
Keywords: Education - Great Britain; Local government - Great Britain; Local government